Analysis of capital structure and roundaboutness. The case of colombian firms - Rahmer, Bruno de Jesús; Herrera-Vega, Juan Carlos; Hernández-Palma, Hugo (Revista de Estudios Andaluces, 2024)
Standard financial theories assume that investment and financing decisions are intertwined. Investment decisions involve selecting assets that generate positive cash flows and maximize shareholder value, while financing decisions involve identifying the optimal mix of debt and equity financing to fund these investments. The main objective of this paper is to analyze the interdependence of assets and liabilities in a sample of Colombian manufacturing firms with varying degrees of roundaboutness (capital-intensive nature). This study employs canonical correlation analysis to determine the interaction between balance sheet components. Subsequently, a threshold regression model is employed to evaluate the influence of financial indicators on the financial performance of firms with heterogeneous capital intensity. The findings reveal that low-capital intensity firms match the maturity structure of assets and liabilities. In firms with low roundaboutness there is a significant relation between throughput, working capital turnover and the proportion of capital expenditure to operating cash flow with ROIC. However, this relationship becomes non-significant at high levels of indebtedness. Conversely, capital-intensive firms exhibit a mismatch between asset and liability maturities, relying on shareholders’ funds to finance long-term assets and inventories. In this group of companies, throughput is positively associated with ROIC regardless of the level of debt, whereas the relationship between working capital turnover and ROIC is not significant until a certain debt threshold is exceeded. The impact of the capital expenditure to operating cash flow ratio on ROIC varies depending on debt levels. Companies with high roundaboutness that exceeds a debt threshold experience a negative impact.